Generation of bovine transgenics using somatic cell nuclear transfer - Stice Steven L; Hodges Craig A (BMC, 2003)
Abstract The ability to produce transgenic animals through the introduction of exogenous DNA has existed for many years. However, past methods available to generate transgenic animals, such as pronuclear microinjection or the use of embryonic stem cells, have either been inefficient or not available in all animals, bovine included. More recently somatic cell nuclear transfer has provided a method to create transgenic animals that overcomes many deficiencies present in other methods. This review summarizes the benefits of using somatic cell nuclear transfer to create bovine transgenics as well as the possible opportunities this method creates for the future.